2019
DOI: 10.3390/ijerph16224477
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Impact of the New York State Smokers’ Quitline on Population-Level Smoking Rates in New York

Abstract: Receiving smoking cessation services from telephone quitlines significantly increases quit success compared with no intervention or other quitting methods. To affect population-level smoking, quitlines must provide a sufficient proportion of smokers with effective interventions. Nationally, quitlines reach around 1% of adult smokers annually. From 2011 through 2016, the average annual reach of the New York State Smokers’ Quitline (NYSSQL) was 2.9%. We used data on the reach and cessation outcomes of NYSSQL to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
0
1
Order By: Relevance
“…Thus, the consistently low budgets of state-run quitlines could be contributing to the relatively stagnant measures of reach over the years. Still, neither budget nor reach were shown to be significant predictors of cessation in our study, and previous studies have suggested that the budget needed to adequately fund quitlines could be prohibitive for some states [36].…”
Section: Main Effectscontrasting
confidence: 93%
“…Thus, the consistently low budgets of state-run quitlines could be contributing to the relatively stagnant measures of reach over the years. Still, neither budget nor reach were shown to be significant predictors of cessation in our study, and previous studies have suggested that the budget needed to adequately fund quitlines could be prohibitive for some states [36].…”
Section: Main Effectscontrasting
confidence: 93%